Penurunan Volume Sampah Dan Budidaya Hidroponik Sebagai Sarana Menanam Sayuran Sehat Di Kampung Menur Pumpungan RW 6 Surabaya Melalui Program Kampung Zero Waste - Kenza Bisri Hariris; Sri Andayani; Febby Rahmatullah Machrusin (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2023)
Vegetables have a nutritional source that is rich in vitamins, minerals, fiber and anti-cocids which really support overall body health. Eating vegetables regularly will have good benefits for the body, one of which is to protect the body from disease and maintain balanced nutritional levels in the body. We can get all the healthy benefits of eating vegetables if we really eat vegetables that do not contain chemicals such as pesticides and herbicides. In this KKN service program, the University of 17 August 1945 Surabaya collaborated with the Surabaya City Environmental Service (DLH). With the contribution of 2 students in one team to help DLH in the MBKM Kampung Zero Waste (KZW) program. Zero Waste, which can be interpreted as 0 waste, is the government's hope that waste in Surabaya can be reduced, although it doesn't have to reach zero. So apart from collecting data on waste reduction in Menur Pumpungan Rw 6, students also created another work program, namely hydroponic cultivation. In Menur Pumpungan village, Rw 6, Surabaya, it is an urban area where there are very few opportunities to eat vegetables that do not contain chemicals. The benefit of this service activity is that the residents of Menur Pumpungan RW 6 can eat fresh vegetables without chemicals which can be planted on a small plot of land using hydroponics as a medium for growing vegetables. Hydroponics is a medium for growing plants without soil, only using water as a substitute for soil. So the work that students carry out in Menur Pumpungan RW 6 village is socializing waste management, reducing existing waste by calculating waste generation and hydroponic cultivation.